IS THE GLASS HALF FULL? - Graham, Tanya M (PINS-Psychology in Society, 2025)
Petersen, I, Bhana, A, Flisher, A J, Swartz, L & Richter, L (eds) (2010) Promoting mental health in scarce-resource contexts: Emerging evidence and practice. Cape Town: HSRC Press. ISBN: 978-0-7969-2303-5 pbk. Pages x + 222. Promoting mental health in scare-resource contexts provides a welcome and stellar contribution to the body of knowledge on mental health promotion that adds the voices of prominent South African academics, researchers and mental health professionals to this field. As its title aptly suggests, the book centres predominantly on the concept of mental health and is situated within a mental health promotion framework. The book aims to provide a theoretical basis for the application of a mental health promotion approach within contexts with limited human, material and environmental resources, poor health infrastructure and underdeveloped health policies. In particular, the book seeks to develop and apply the theoretical premises of mental health promotion to the conditions and imperatives of LMICs, and illustrate their merit through using exemplars from different mental health interventions in these contexts. The book examines mental health using a lifespan approach to understanding risk and protective factors for human development, and demonstrates how interventions can be designed and targeted to promote wellbeing at different life stages. This review discusses some of the core critical debates that surround the conceptual basis of the book. The review then examines the specific chapters of the book and evaluates its particular relevance for LMICs.